The right to health and the human rights reform in Mexico - Robles Garza, Magda Yadira (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
The research presented here aims to analyze the constitutional development of the right to health in Mexico from the social constitutionalism of 1917. The jurisprudential treatment given by the federal courts in order to demonstrate that the configuration process has set the limits and scope of the right will be observed from this legislative development. This will take us to examine the impact that the constitutional reform of 2011 may have on the judicial protection of that right as a result of the application of the new criteria of constitutional justice which this reform brought with it.